Invasion of non-indigenous suckermouth armoured catfish of the genus Pterygoplichthys (Loricariidae) in the East Kolkata Wetlands: stakeholders’ perception - Hussan, Ajmal; Sundaray, J. K.; Mandal, R. N.; Hoque, Farhana; Das, Arabinda; Chakrabarti, P. P.; Adhikari, S. (Indian Journal of Fisheries, 2019)
Rapid spread and population increase of suckermouth armoured catfishes belonging to the genus Pterygoplichthys(Loricariidae) in the East Kolkata Wetlands (EKW) in recent times is of increasing concern, because of the notable possibility that these non-native catfishes are adversely affecting fish germplasm and commercial fishery of this unique ecosystem. To study the present status of these loricariids and the invasion and impact dynamics in EKW ecosystems, field survey was conducted over a water spread area of 670 ha, comprising 120 fishermen (N2 = 120) of 30 farms (N1 = 30), between February and October, 2017 through a pre-tested, open-ended structured schedule. A total of 943 specimens of Pterygoplichthysspp. were collected and analysed for abundance, length-weight parameters, gonado-somatic index and relative fecundity. Pterygoplichthysspp. occurred at 29 (97%) of 30 surveyed farms and approximately 70% of the farm owners perceived that these fishes posed moderate to serious economic impact. Fish production cutback, small indigenous fish (particularly,Puntius spp.) depredation and bottom structure alteration are among the major negatives perceived; a positive note in terms of soil-bound nutrient release was reported by a few fishermen (1%). Channel through which sewage water intake occurred by gravitation has been perceived to be the main route of entry (77%), with significantly higher abundance around the periphery of the pond. Almost 80% respondents perceived an increased occurrence of these fishes over the last four years, with seasonal pattern of abundance. While culling of suckermouthafter harvest was the most common method adopted to reduce population, multi-layer screening in the inlet of sewage water into pond is perceived as most sought solution for control. Average direct and indirect financial losses due to Pterygoplichthys spp. in EKW was calculated as`0.092 lakh ha-1yr-1, which points towards mounting pressure of loricariids in already dwindling economics and biodiversity of EKW.Keywords: East Kolkata Wetlands, Biodiversity, Pterygoplichthys,Invasion, Sewage